Windows Phone 8 Recipes A Problem-Solution Approach - Lalonde, Lori; Totzke, David R. (Apress : Imprint: Apress, 2013)
Windows Phone 8 Recipes is a problem-solution based guide to the Windows Phone 8 platform. Recipes are grouped according to features of the platform and ways of interacting with the device. Solutions are given in C# and XAML, so you can take your existing .NET skills and apply them to this exciting new venture. Not sure how to get started? No need to worry, there's a recipe for that! Always wondered what it takes to add cool features like gesture support, maps integration, or speech recognition into your app? We've got it covered! Already have a portfolio of Windows Phone 7 apps that needs to be upgraded? We have a recipe for that too! The book starts by guiding you through the setup of your development environment, including links to useful tools and resources. Core chapters range from coding live tiles and notifications to interacting with the camera and location sensor. Later chapters cover external services including Windows Azure Mobile Services, the Live SDK, and the Microsoft Advertising SDK, so you can take your app to a professional level. Finally, you'll find out how to publish and maintain your app in the Windows Phone Store.  Whether you're migrating from Windows Phone 7 or starting from scratch, Windows Phone 8 Recipes has the code you need to bring your app idea to life.